A model to predict the expansion of trioza erytreae throughout the iberian peninsula using a pest risk analysis approach - Benhadi-Marín, Jacinto (2020)
Assessing the potential of spread of an introduced crop pest in a new country is crucial to anticipating its effects on crop production and deriving phytosanitary management toward reducing potential negative effects. Citrus production represents a key agricultural activity throughout the Mediterranean basin. The African citrus psyllid Trioza erytreae (del Guercio, 1918) (Hemiptera: Triozidae) is a natural vector of Candidatus liberibacter spp., the causal agent of the harmful disease huanglongbing (HLB) or “citrus greening disease”. In continental Europe, T. erytreae was detected for the first time in northwestern Spain in 2014. Pest risk analysis (PRA) approaches, such as modeling, consider both time and space components to predict the potential distribution of pests in a given region. In this work, we aim to parameterize a model able to predict the expected spread of T. erytreae in the Iberian Peninsula using three types of PRA models. The kernel model with two hypothetical entry points accurately predicted the distribution of T. erytreae with respect to latitude. This model should be further refined and validated to support decision-makers in the adoption of timely and successful management and regulatory measures against the spread of T. erytreae to other citrus-producing areas in Europe.